An optimal planning approach for EV charging station installation in Distribution Network - Kara G.; Barnwal A.K.; Verma M.K. (My University, 2025)
The increasing adoption of electric vehicles (EVs) over conventional internal combustion engine based vehicles has led to the need for building charging infrastructure for sustaining the popularity of EVs. Installation of charging facility means an additional load demand increase for the distribution system. The location, size and type of charging station must be optimally planned so as to minimize the effect of EV charging station load and ensure the safe operation of the network. In this work, various case studies are performed to investigate the impact of location, number and type of charging station and subsequently optimal planning is done taking into the account the charging need of EV users. To validate the effectiveness, the results of optimal planning are compared to random planning. Further, it was observed that voltage limits at some buses are violated which is corrected by introducing a DG unit of optimal size at optimal location. The entire study has been performed on the IEEE 33 bus distribution system. © 2022 IEEE.